1971
DOI: 10.1111/j.1365-2672.1971.tb02280.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Media in Air Sampling: A Review

Abstract: Summary. Under field conditions wanted micro‐organisms are often present in the air in small numbers and form a small proportion of the total flora. Selective techniques would be useful, but may be difficult to devise as airborne micro‐organisms are easily damaged and passing air over organisms deposited on slit sampler plates may be traumatic. Selective media may be avoided by using indicator media or animal inoculation, or the organisms may be transferred to selective conditions after some growth has taken p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 69 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…It is possible that low relative humidity at the time of the sampling decreased the number of viable organisms recovered, as had been reported previously (4). Another possible reason for low bacterial counts is the mechanical trauma and dehydration the organisms sustain during the sampling procedure, caused by forcing them through small orifices and onto the agar surface at high speed (13). It is also possible that the numbers of organisms present in shower or tap water were too low to generate large numbers of aerosolized organisms.…”
Section: Discussionmentioning
confidence: 74%
“…It is possible that low relative humidity at the time of the sampling decreased the number of viable organisms recovered, as had been reported previously (4). Another possible reason for low bacterial counts is the mechanical trauma and dehydration the organisms sustain during the sampling procedure, caused by forcing them through small orifices and onto the agar surface at high speed (13). It is also possible that the numbers of organisms present in shower or tap water were too low to generate large numbers of aerosolized organisms.…”
Section: Discussionmentioning
confidence: 74%
“…In Study 2, exhaustive testing of the special media used, as discussed by Kingston (1971), was not done. However, as Kingston noted, MacConkey agar proved satisfactory for recovery of coliforms from air (Bound and Atkinson, 1966), and recovery here of staphylococci and streptococci in considerable numbers indicates that the media used were suitable.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of coliform bacteria and viruses falling out onto surfaces in the bathroom after flushing indicated that these organisms remain airborne long enough to settle on surfaces throughout the bathroom. The number of E. coli detected on the agar plates is probably a minimal value since airborne bacteria are damaged during aerosolization and by environmental stresses, making growth on selective media more difficult (13). These data also do not take into account the accumulation of organisms on the walls and other surfaces of the bathroom.…”
Section: Considerable Numbers Of Bacteria and Virusesmentioning
confidence: 99%